Fungsi Sosial “Kisah Situ Bagendit” Sebagai Edukasi Mitigasi Bencana Nonstruktural - Gisella Orlanova Ramadhanti; Surahmat (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to examine the social function of the folktale Kisah Situ Bagendit as a medium for non-structural disaster mitigation education. The study is motivated by the high risk of flood disasters in Indonesia and the importance of mitigation efforts based on local wisdom. This research employs a descriptive qualitative method using Ian Watt’s sociology of literature approach, which includes the social context of the author, literary works as reflections of society, and the social function of literature. The research data consist of textual excerpts from Kisah Situ Bagendit that contain social values and disaster mitigation messages. Data were collected through documentation techniques and analyzed interpretatively. The results indicate that the folktale reflects social conditions in society, particularly social inequality, greed, and the consequences of environmental destruction. Furthermore, the story contains educational values related to the causes of disasters, the importance of environmental preservation, and collective awareness in preventing and dealing with disasters. Therefore, folktales can function as a medium for non-structural disaster mitigation education based on local wisdom.